The Effect of Potty Chair Training on Family Empowerment in Toilet Training for Toddler in Early Childhood Education - Atik Badi'ah; Yustiana Olfah; Titik Endarwati; Ni Ketut Mendri; Heru Santoso Wahito Nugroho (Health Notions, 2022)
Background: According to Wong (2013), in 5 million children in the United States the prevalence of enuresis in children aged 5 years is 7% for men and 3% for girls, in children aged 10 years the prevalence is 3% for boys and 2% for girls, in children aged 18 years the prevalence is 1% for boys and is very rare for girls. The role of nurses as educators is to assist clients in increasing the level of health knowledge, symptoms of illness and even actions given, so that behavior changes occur from clients after health education is done. One effort that can be done as a function of nurses is to educate children how to deal with enuresis by providing toilet training. Based on a preliminary study conducted, the data showed that the number of toddlers (1-3 years) in early childhood education in Yogyakarta was 100 people consisting of 55 men and 45 women. . From the results of observations and information from Early Childhood Education teachers obtained data from 100 toddlers aged 1-3 years, there were 90 toddlers aged 1-3 years (90%) who were in Early Childhood Education were still using posters. Purpose: The influence of potty chair training on family empowerment in toilet training toddler (1-3 years) in early childhood education. Methods: Type of research quasi experiment with pre test post test with control group design. This design had a comparison group (control), observations were made twice. The first observation was to find out family empowerment in toilet training for toddlers (1-3 years) in early childhood education before being given training using a potty chair and a second observation after being given training using a potty chair. Sampling was done by purposive sampling with the criteria of mothers who have toddlers (1-3 years) in early childhood education. Data from the examination results were analyzed analytically using the t-test and Wilcoxon test. Results: Family empowerment in toilet training for toddlers in the experimental group or pre-test and post-test treatment with p = 0,00 and in the control group with p = 0,00. Conclusion: There is an effect of potty chair training on family empowerment in toilet toddler training (1-3 years) Early Childhood Education. Keywords: potty chair training; family empowerment; toilet training; early childhood education